The morphogenesis of marandu palisadegrass at fixed or variable heights in different seasons of the year (Bioscience Journal, 2020)
Height variations in a sward over the year may be efficient for increasing plant growth, compared with maintenance of the sward at a constant height. Thus, this experiment was conducted from February 2013 to May 2014 to characterise the development of Urochloa brizantha syn. Brachiaria brizantha cv. Marandu (marandu palisadegrass), managed under three defoliation strategies: constant height (30 cm during the entire experimental period), increasing height (15 cm in the winter, 30 cm in the spring, and 45 cm in the summer), and decreasing height (45 cm in the winter, 30 cm in the spring, and 15 cm in the summer). The experimental design was completely randomised, in a split-plot arrangement, with four replicates. Phyllochron was higher in the winter, but leaf and stem elongation rates and the number of live leaves per tiller were lower compared with the spring and summer. In the summer, the swards under increasing height displayed a higher phyllochron than those under decreasing and constant height. When comparing seasons, the highest leaf senescence rate occurred in spring. In the winter, the sward with increasing height had shorter leaves and stems, in contrast to the summer. The sward under decreasing height showed a high stem elongation rate in the spring. Marandu palisadegrass has great flexibility in terms of defoliation management and a typical seasonal development pattern. Modifying the sward height results in a gradual change in the development of marandu palisadegrass and generates residual effects on the subsequent season.